Motif Menonton Vlog "Keluarga Beti" Channel Youtube Arif Muhammad - Didik Hariyanto; Aninda Pinasti Putri Mariyanto (Kanal: Jurnal Ilmu Komunikasi, 2020)
This study aims to determine the motives of vlog audience "beti family". This study uses in-depth interviews, and documentation. Measurement of motifs in this study uses McQuail's motive theory, namely: information motives, personal identity motives, social interaction motives, and entertainment motives. The Uses and Gratification Theory assumes that media is not all powerful, which has a high power, that is to its users. Media users have the choice of consuming media to satisfy their needs. The "Beti Family" vlog Arif Muhammad's youtube channel is the research subject chosen by the researcher. This is because one of the drama vlogs on YouTube is the most popular community and is often included in YouTube's tranding column. The results that can be dominant in the motives of social interaction and entertainment motives. The informant's answer about the motives of social interaction because it allows the informant to interact with each other and get new conversations about the uniqueness contained in this vlog. And for answers about entertainment motives because they want to get entertainment and want to get rid of boredom.